Effect of Snake and Ladder Game on Knowledge, Attitude, and Expressed Practices Regarding Personal Hygiene among Primary School Children: A Randomized Controlled trial - Sanju Pukhraj, Khawa; Deol, Rupinder; Malar Kodi, S. (International Journal of Nursing Research, 2023)
Introduction: Children are most vulnerable group; therefore, they are more prone to various health-related problems. They should be taught regarding importance of personal hygiene to maintain good health. Primary school children learn mainly through imitation and therefore play method enhances better learning. Snake and ladder game is very familiar to children so it will enhance better learning. Materials and Methods: A prospective, open-label, parallel group, randomized controlled trial was conducted on a sample size of 300 primary school children with disproportionate stratified random sampling technique. The interventional group (n = 150) received snake and ladder game regarding personal hygiene for a period of 5 days with pre-test on day 1 followed by intervention with the help of snake and ladder game focusing on 10 different components of personal hygiene such as brushing of teeth, bathing, hair wash, nail cutting, hand washing, clean clothes, wearing foot wear, and ear, food and water hygiene and subsequently post-test on day 5. The control group (n = 150) received routine activities. A self-structured questionnaire was used to assess knowledge, attitude, and expressed practices regarding personal hygiene among children in both the groups. Mann–Whitney U and Wilcoxon signed-rank tests were used for analysis. Results: There was a significant improvement in knowledge, attitude, and expressed practices regarding personal hygiene among children in interventional group as compared to control group (p < 0.05). Conclusion: Snake and ladder game was effective in improving knowledge that ultimately improved attitude and practices regarding personal hygiene among primary school children